PERLINDUNGAN HUKUM NOTARIS TERKAIT GUGATAN PENGHADAP ATAS PENGGUNAAN SAKSI INSTRUMENTER DALAM PEMBUATAN AKTA AUTENTIK - Farah Ferida Indra Chaniago; Yuliana Setiadi; Refki Ridwan (Bajang Institute, 2025)
One form of obligation and responsibility of a Notary is to present an instrumental witness in the process of making an authentic deed as regulated in Article 16 paragraph (1) letter m and Article 40 Law Number 2 of 2014 concerning amendments to Law Number 30 of 2004 concerning the position of Notary, hereinafter referred to as UUJN. In its implementation, lawsuits are often found related to the absence of instrumental witnesses. So this research discusses the responsibilities of Notaries regarding the use of instrumental witnesses in authentic deeds and the legal protection of Notaries regarding lawsuits against the use of instrumental witnesses in authentic deeds. The theory used in this research is authentication and legal protection according to Satjipto Rahardjo.The research method used in this research is normative juridical, the research approach used is the case approach, statutory approach, analytical approach and conceptual approach and the sources of legal materials used are primary, secondary and tertiary legal materials with techniques for collecting legal materials carried out by collecting library materials and analyzing legal materials using systematic legal interpretation and grammatical interpretation.From this research, it can be seen that the Notary is responsible for fulfilling the formal requirements in an authentic deed, one of which is by presenting two (2) instrumental witnesses, because the result of not presenting all the instrumental witnesses causes the evidentiary power of the Notarial deed as an authentic deed to only be recognized as a deed that has personal evidentiary power. So that in the future there will be no more lawsuits related to instrumental witnesses, it is necessary to reform the law, namely by changing the UUJN in article 40 regarding instrumental witnesses. With this legal reform, it is hoped that in the future it will be possible to improve legal protection for Notaries regarding the use of instrumental witnesses.